Reduction of the measurand estimate bias for nonlinear model equation - Botsiura, O. A.; Zakharov, I.; Neyezhmakov, P. (Journal of Physics: Conf. Series, 2018)
The biases arising in the calculation of the measurand estimate at nonlinear measurement models are considered. The possibility of reducing these biases by applying the finite increments method is shown.
Keywords: measurand estimate bias; nonlinear model equation